The very cranky bear - "Bland , Nica" (Hodder children's books; London., 2008)
In the Jingle, jangle jungle, four friends$1 (BMoose, Lion, Zebra, and Sheep$1 (Bencounter a very cranky bear. Each animal attempts to cheer him up, but it's plain, boring Sheep who has the answer. This humorous story carries the message: don't underestimate the quiet ones; sometimes a little thought is all you need to solve a problem instead of rushing to immediate action.s